Vocabulary Instruction for the Development of American Sign Language in Young Deaf Children: An Investigation into Teacher Knowledge and Practice. - Pizzo, Lianna (Sign Language Studies)
Vocabulary development is an essential linguistic component of later English literacy skills (National Reading Panel 2000). However, very few studies have addressed the promotion of vocabulary development in deaf children who are American Sign Language users (Luckner and Cooke 2010). Therefore, this qualitative collective case study examined the nature of vocabulary instruction by four early childhood teachers of deaf children (TODs) in two classrooms. Findings indicate that the components of a four-part vocabulary program (Graves 2006) account for the nature of vocabulary instruction; however, the teachers also used specific strategies that are linguistically relevant to ASL and other visual languages. Furthermore, the interplay of teacher knowledge of the learners, curricula, and pedagogy informed the teachers' instructional planning and decision-making. Implications of this study include identification of the varying roles that teacher knowledge, experience, and evidence play in guiding ASL vocabulary instruction for TODs.